Representation of Pseudobulbar Effect in the ‘Joker’ Movie (International Online Journal of Language, Communication, and Humanities (INSANIAH), 2023)
Pseudobulbar affect (PBA) is a brain disorder that causes laughter or crying but does not match the feelings. Mental illness often appears as a commodity for filmmakers. Like in the 'Joker' movie which uses pseudobulbar affect as an object to the story. The aim of this research is to reveal the representation of pseudobulbar affect in the 'Joker' movie. This qualitative research using Popular Culture Theory with Roland Barthes semiotic analysis method with it’s three elements (denotation, connotation, myth). This research reveals that pseudobulbar affect is represented as a disease that makes a person laughing and crying without appropriate feeling, incurable, less known to the public, trampled by people around him. This research also found a shift and stabilization of myth of Pseudobulbar affect. The representation of pseudobulbar affect in the 'Joker' movie creates a bad view for the audience because of the selfish interests of the ruling classes only.